Antifungal properties of whey fermented by lactic acid bacteria in films for the preservation of cheese slices. (2nd June 2022) - Dopazo, Victor; Luz, Carlos; Calpe, Jorge; Vila‐Donat, Pilar; Rodríguez, Lorena; Meca, Giuseppe
Abstract : Fungal deterioration by Penicillium species in refrigerated storage conditions is one of the main risk factors for health issues and food waste in the dairy industry. The purpose of this study was to evaluate the antifungal properties of a plastic film carrying whey fermented by lactic acid bacteria (LAB). The results evidenced that a film containing whey fermented using lactic acid bacteria inhibited the growth of Penicillium commune, Penicillium verrucosum and Penicillium solitum for 23, 20 and 17 days, respectively. Abstract : Workflow to develop an active film with LAB‐fermented whey for a novel application as a biopreservative of cheese.